2023
DOI: 10.3390/s23187952
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Six Semi-Automated Tumour Delineation Methods on [18F] Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (FDG PET/CT) in Patients with Head and Neck Cancer

Francesco Bianconi,
Roberto Salis,
Mario Luca Fravolini
et al.

Abstract: Background. Head and neck cancer (HNC) is the seventh most common neoplastic disorder at the global level. Contouring HNC lesions on [18F] Fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) scans plays a fundamental role for diagnosis, risk assessment, radiotherapy planning and post-treatment evaluation. However, manual contouring is a lengthy and tedious procedure which requires significant effort from the clinician. Methods. We evaluated the performance of six hand-crafted, trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Nestle’s method was originally developed to delineate target volume in radiotherapy planning [ 23 ]. It is one of the threshold-based methods that used the threshold calculated from FDG uptake in the tumor and background on a case-by-case basis, and has demonstrated strong inter-patient stability in a previous study that compared PET segmentation methods [ 37 , 38 ]. In several previous studies, the clinical value of tumor PET radiomic parameters were successfully demonstrated using Nestle’s method, suggesting the clinical relevance of this method [ 20 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nestle’s method was originally developed to delineate target volume in radiotherapy planning [ 23 ]. It is one of the threshold-based methods that used the threshold calculated from FDG uptake in the tumor and background on a case-by-case basis, and has demonstrated strong inter-patient stability in a previous study that compared PET segmentation methods [ 37 , 38 ]. In several previous studies, the clinical value of tumor PET radiomic parameters were successfully demonstrated using Nestle’s method, suggesting the clinical relevance of this method [ 20 , 39 ].…”
Section: Discussionmentioning
confidence: 99%